The New Instructional Leadership: Creating Data-Driven Instructional Systems in School(2007). Issue 3 (May 2015) - Halverson, Richard; Grigg, Jeffrey; Prichett, Reid; Thomas, Chris
The recent press for high-stakes accountability has challenged school leaders to use data to guide the practices of teaching and learning. This article considers how local school leaders build data-driven instructional systems to systematically improve student learning. Such systems are presented as a framework involving data acquisition, data reflection, program alignment and integration, program design, formative feedback, and test preparation. The article reviews data collected in a yearlong study of four schools to describe how leaders structure opportunities to engage in data-driven decision making.